Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 7 - Algebraic Fractions - 7.1 - Simplifying Algebraic Fractions - Problem Set 7.1 - Page 282: 72



Work Step by Step

Using the rule $\frac{x^{a}}{x^{b}}=x^{a-b}$, we obtain: $\frac{-44a^{3}b^{4}}{4a^{3}b^{6}}$ $\frac{-44}{4}\times\frac{a^{3}}{a^{3}}\times\frac{b^{4}}{b^{6}}$ $=-11\times a^{3-3}\times b^{4-6}$ $=-11\times a^{0}\times b^{-2}$ $=-11\times 1\times \frac{1}{b^{2}}$ $=\frac{-11}{b^{2}}$ $=-\frac{11}{b^{2}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.